2018
DOI: 10.1038/s41598-018-22278-w
|View full text |Cite
|
Sign up to set email alerts
|

A CREB2-targeting microRNA is required for long-term memory after single-trial learning

Abstract: Although single-trial induced long-term memories (LTM) have been of major interest in neuroscience, how LTM can form after a single episode of learning remains largely unknown. We hypothesized that the removal of molecular inhibitory constraints by microRNAs (miRNAs) plays an important role in this process. To test this hypothesis, first we constructed small non-coding RNA (sncRNA) cDNA libraries from the CNS of Lymnaea stagnalis subjected to a single conditioning trial. Then, by next generation sequencing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 46 publications
1
44
1
4
Order By: Relevance
“…Finally, Cage-MB-in was applied to measure the change in abundance of miRNA-21 during drug treatment. As an inhibitor of Dicer activity 63 , poly-L-lysine (PLL) can reduce the production of mature miRNA-21, which was validated by qRT-PCR ( Supplementary Fig. S39).…”
Section: Resultsmentioning
confidence: 90%
“…Finally, Cage-MB-in was applied to measure the change in abundance of miRNA-21 during drug treatment. As an inhibitor of Dicer activity 63 , poly-L-lysine (PLL) can reduce the production of mature miRNA-21, which was validated by qRT-PCR ( Supplementary Fig. S39).…”
Section: Resultsmentioning
confidence: 90%
“…Mir23b down-regulation with a single training trial may be temporally limited such that it effectively supports 24 h, but not 48 h, memory. However, MiRs are also implicated in multiday long-term memories (Korneev et al 2018). It will be of interest to examine differences in mRNA expression in trained and nontrained cohorts at 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impairment of microRNA biosynthesis in dopaminergic neurons due to suppression or depletion of Dicer (tissue-specific inducible suppression) causes dopaminergic cell dysfunction, while pharmacological stimulation is neuroprotective (Chmielarz et al, 2017). In addition, the pharmacological inhibition of Dicer activity with poly-lysine (Poly-L-lysine hydrobromide) disrupts formation of a conditioned reflex with single-trial induced LTM in the mollusk Lymnaea stagnalis (Korneev et al, 2018) and impairs formation of the conditioned defense reflex in the mollusk Helix (Grinkevich, 2019). Thus, the last two studies show that short-term Dicer dysfunction can lead not to improvement, but to impairment of LTM.…”
Section: The Effect Of Microrna Biogenesis Disorders On Ltm Formationmentioning
confidence: 99%
“…This microRNA is being intensively studied both in connection with the mechanisms of LTM and with various cognitive pathologies, and its functions are very diverse. It has been shown that activation of miR-137 is re quired for long-term memory formation in the pond snail Lymnaea (Korneev et al, 2018). At the same time, miR-137 inhibits the transcription factor CREB2, a negative regulator of the expression of genes necessary for LTM formation.…”
Section: Micrornas That Can Influence Learning and Long-term Memory Imentioning
confidence: 99%